MANAJEMEN PROMOSI KESEHATAN PADA MASA TANGGAP DARURAT BENCANA GUNUNG MERAPI YOGYAKARTA - , Fauzie Rahman ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: The eruption of Mount Merapi in Yogyakarta has caused dangerous impact to the peopleâs health. Health promotion efforts are needed in the affected areas, especially in refugee camps. In order to minimize health impacts to be inflicted on refugees. The management of health promotion needs to be assessed to evaluate the process in order to develop the better health promotion for disaster situation. Objectives: To determine the management of health promotion at the time of the disaster emergency response during Mount Merapi eruption. Methods: This was a qualitative study using case study design. In-depth interviews and documentation study were used to obtain data on health promotion management. The informants were the health promotion program manager of the Provincial Health Office in Yogyakarta, Sleman District Health Office, and manager from health service division of Indonesian Red Cross. To ensure the validity of the data, we used triangulation of data and sources. Result: All aspects of health promotion management, including planning, organizing, implementing, monitoring, financing and evaluation, were assessed. Planning process included health assessment in the refugee camps to determine health problems, the needs for program implementation, and targets of the program based on the duties and functions of health promotion programs. Implementation of health promotion programs used integrated strategies which supported by customized media based on targeted audience. Program funding comes from the national plan and budget (APBN) and regional plan and budget (APBD) and social funds. Monitoring and evaluation were carried out at the time and after the program completed, the purposes of these activities is to acknowledge the result and bottleneck which is appear during the health promotion process. Until the emergency response ended, there was no outbreak, the morbidity rate was decreased and the infection cases were under control. However, some problems were found such as limited human resources and facilities, health promotion standards for the eruption of Mount Merapi also have not been enabled. Conclusion: The management of health promotion during the eruption of Mount Merapi was considered quite effective. The improvement of partnership with other agencies is needed as well as surge capacity for the health promotion program during emergency response.